Africa's security landscape of securitised-development and human rights issues. Issue 1 (2nd January 2022) - Kumah-Abiwu, Felix
ABSTRACT: Africa's security landscape has been experiencing securitised-development practices through counterterrorism activities from donor countries engaged in the 'Global War on Terror' (GWOT). While some African governments continue to 'benefit' from the securitised-development agenda, critiques argue that there are human rights concerns that are connected to the practice of securitised-development. They have emphasised how some African governments and military actors involved in fighting the GWOT are also faced with human rights issues. To explore these issues, the article examines the securitised-development agenda in Kenya and Uganda and its impact on human rights. The article argues that the securitised-development practice is characterised by underlying contradictions involving the fight against terrorism and the accompanying human rights concerns in these countries.